Building defect : case study at Taman Seri Indah , Pulau Pinang - Nur Diyana, Md. Kasim (2009)
Malaysia is one of the developing countries and many projects are being implemented. Currently, which some of the projects involve construction of buildings. The construction industry helps to generate the nation’s economy as well as providing benefits to construction companies. But some of these firms acted unprofessionally by involving in projects that do not meet the standard especially in housing development. There are a lot of defects to the houses purchased by house buyers especially in terms of material and workmanship. This study is conducted to identify types of building defect occur in building and to identify causes of building defect occur in building. Besides that, study on building defects which occur at case study area also has been done. The resident satisfactions level on their housing after defect liability period also being analyzed. The study area is located at Taman Seri Indah, Penang. The methodology adopted is through literature review and interview with the developer and house buyers. The data are collected through questionnaire that had been distributed to the parties involve in construction and the house buyers at study area. Types and causes of building defect also can be identified according to survey that has been done to people that involve in construction industry. The results also show the poor workmanship is the major contributor to poor quality of construction. In order to minimize the problem, the contactor has to provide workers with necessary experience and skills. The finding of this study can be used for future references.